THE MAJESTIC 8: ROLES OF SONG AS LYRICAL AUDIO OF LISTENING MEDIA - Nurbani, Armelia Nungki (E-Link Journal, 2020)
The aim of this research was to find out the roles of songs in teaching listening at Senior High School. Teachers can use some media that are suitable with the condition of the class and students. For that reason, song is one of media that is familiar for students. Descriptive qualitative was the approach of this research. The data were derived from interview, observation and documentation. The interview were conducted by 7 participants consisting of 6 students and 1 teacher. The subject of this research was the twelve grade students of one of Senior High School in Surabaya. This study found 3 roles and 5 benefits of songs in teaching listening at Senior High School. The result of roles are 1) song is a cozy medium to teach listening. 2) song is used to entertain students in listening class. 3) song is used to motivate students to learn English in the classroom. Besides, the result of benefits are 1) the students can learn vocabulary and meaning. 2) the students can learn pronunciation. 3) the students can train their listening skill. 4) the students can enjoy the listening class. 5) the students became active and confident in the class. In conclusion, songs became one of good media in teaching listening because the students can feel comfortable, happy, and do not feel bored when they are in listening session. To all intens and purposes, there is a need to be conducted with having many participants for further research both different school or level. This is to get rich of the data in order to have more concrete data. Keywords: Roles of song, listening media